Noncanonical shimmy and protection against it - Шифрин, Борис Меерович (Eastern-European Journal of Enterprise Technologies, 2012)
It is suggested to difference the tasks of canonical and noncanonical shimmy. Three mechanisms of noncanonical shimmy are described, resulting in intensive transversal-forward to the vibrations of supports of undercarriage. A stand is presented for the supervision of noncanonical shimmy and the program of protecting against it is offered